Electrostatic spinning PVDF (polyvinylidene fluoride) nanofiber membrane for sewage treatment as well as preparation method and application of electrostatic spinning PVDF nanofiber membrane

By introducing a polydopamine coating and adding surface-modified nano-TiO2 particles to the surface of PVDF nanofiber membranes, the prepared PVDF/TiO2/PVP nanofiber membranes solve the problems of poor hydrophilicity and easy fouling, and improve the removal efficiency of organic pollutants and heavy metal ions.

CN121110271APending Publication Date: 2025-12-12JILIN UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511318329.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing electrospun PVDF nanofiber membranes have problems such as poor hydrophilicity, easy fouling, and low removal efficiency for certain pollutants in wastewater treatment.

Method used

A PVDF/TiO2/PVP nanofiber membrane was prepared by introducing a polydopamine coating on the surface of the PVDF nanofiber membrane and adding surface-modified nano-TiO2 particles. The preparation method included electrospinning and a simple post-processing process.

Benefits of technology

It significantly improves the hydrophilicity and antifouling properties of nanofiber membranes, enhances the photocatalytic performance of organic pollutants, and achieves efficient retention of heavy metal ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121110271A_ABST
    Figure CN121110271A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, in particular to an electrostatic spinning PVDF nanofiber membrane for sewage treatment and a preparation method and application of the electrostatic spinning PVDF nanofiber membrane. The preparation method comprises the following steps: dissolving PVDF (Polyvinylidene Fluoride) particles in a mixed solvent of DMF (Dimethyl Formamide) and acetone, adding nano TiO2 particles subjected to APTES (Aminopropyltriethoxysilane) surface modification, and adding PVP (Polyvinyl Pyrrolidone) into the solution to obtain a uniform spinning solution; spinning by adopting electrostatic spinning equipment to obtain a PVDF / TiO2 / PVP nanofiber membrane; the nanofiber membrane is soaked in a sodium hydroxide solution, then the membrane is soaked in a Tris-HCl buffer solution containing dopamine, and the final electrostatic spinning PVDF nanofiber membrane is obtained. The average diameter of nanofibers of the nanofiber membrane is 200-300nm, the porosity of the membrane is 70-80%, and the water contact angle is less than 60 degrees; when the nanofiber membrane is used for treating sewage containing organic pollutants and heavy metal ions, the removal rate of the nanofiber membrane on methyl orange can reach 95% or above; the rejection rate of copper ions can reach 90% or above; the removal efficiency of organic pollutants and heavy metal ions is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment technology, specifically to an electrospun PVDF nanofiber membrane and its preparation method, as well as the application of the nanofiber membrane in wastewater treatment. Background Technology

[0002] With industrial development and population growth, wastewater treatment has become one of the most significant environmental challenges facing the world. Traditional wastewater treatment methods, such as biological treatment and chemical precipitation, suffer from low efficiency, high energy consumption, and secondary pollution. Membrane separation technology, as a highly efficient and energy-saving wastewater treatment method, has received widespread attention in recent years. Among them, nanofiber membranes, due to their high specific surface area, high porosity, and controllable pore size distribution, have shown great potential in wastewater treatment.

[0003] Polyvinylidene fluoride (PVDF) is a polymer material with excellent chemical, mechanical, and thermal stability, and is widely used in membrane separation. Electrospinning is an effective method for preparing nanofibers, enabling direct and continuous fabrication with good fiber structure tunability, simple operation, and high production efficiency. However, existing electrospun PVDF nanofiber membranes still have some problems in wastewater treatment, such as poor hydrophilicity, susceptibility to fouling, and low removal efficiency for certain pollutants. Therefore, this invention aims to develop a new method for preparing electrospun PVDF nanofiber membranes for efficient wastewater treatment, which has significant practical implications. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides an electrospun PVDF nanofiber membrane for wastewater treatment, the preparation method of which is as follows:

[0005] Step 1: Preparation of spinning solution:

[0006] Polyvinylidene fluoride (PVDF) particles were dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and acetone, and stirred at 55-65°C for 6-10 hours to obtain a PVDF solution with a mass fraction of 16-20%. Nano-TiO2 particles modified with 3-aminopropyltriethoxysilane (APTES) were added to the obtained PVDF solution, wherein the mass of the nano-TiO2 particles was 3-7% of the mass of PVDF. Polyvinylpyrrolidone (PVP) was then added to the solution, wherein the mass of the polyvinylpyrrolidone was 8-12% of the mass of PVDF, and stirring was continued for 1-3 hours to obtain a uniform spinning solution.

[0007] Step 2, electrospinning:

[0008] The obtained spinning solution was loaded into a syringe with a metal needle, and electrospinning was performed using an electrospinning device. The electrospinning parameters were set as follows: voltage 18-22kV, distance between needle and collector 13-17cm, feed rate 0.4-0.6mL / h, ambient temperature 23-27℃, and humidity 35-45%. PVDF / TiO2 / PVP nanofiber membrane was obtained on the collector.

[0009] Step 3, Post-processing:

[0010] The PVDF / TiO2 / PVP nanofiber membrane was immersed in a 4-6% sodium hydroxide solution and treated at 28-32°C for 1.5-2.5 hours, then rinsed with deionized water until neutral. The membrane was then immersed in a Tris-HCl buffer solution containing dopamine and reacted at room temperature for 10-14 hours to allow dopamine to self-polymerize on the membrane surface to form a polydopamine (PDA) coating, thus obtaining the final electrospun PVDF nanofiber membrane.

[0011] Furthermore, in step one, the volume ratio of N,N-dimethylformamide (DMF) to acetone in the mixed solvent of N,N-dimethylformamide (DMF) and acetone is 2.8-3.2:1.8-2.2.

[0012] Preferably, the volume ratio of N,N-dimethylformamide to acetone can be 2.8:1.8, 2.9:1.9, 3:2, 3.1:2.1, or 3.2:2.2.

[0013] Further, in step one, the surface modification method of the nano-TiO2 particles is as follows: the nano-TiO2 particles are dispersed in ethanol, APTES is added, the mass ratio of APTES to nano-TiO2 particles is 1:8-12, the reaction is stirred at 45-55℃ for 3-5 hours, and then centrifuged, washed and dried to obtain nano-TiO2 particles modified with 3-aminopropyltriethoxysilane (APTES).

[0014] Preferably, the nano-TiO2 particles are dispersed in ethanol by ultrasonic dispersion for 25-35 minutes.

[0015] Preferably, the mass ratio of APTES to nano-TiO2 particles can be 1:8; 1:9; 1:10; 1:11; 1:12.

[0016] Furthermore, in step two, the metal needle is of model 20-24G.

[0017] Furthermore, in step three, the concentration of dopamine in the Tris-HCl buffer solution containing dopamine is 1.8-2.2 mg / mL, and the pH value of the buffer solution is 8.3-8.7.

[0018] Preferably, in the Tris-HCl buffer solution containing dopamine, the concentration of dopamine can be 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 2.1 mg / mL, or 2.2 mg / mL.

[0019] Furthermore, in step three, the membrane treated with sodium hydroxide solution is rinsed with deionized water 3-5 times, with each rinsing lasting 5-10 minutes.

[0020] The electrospun PVDF nanofiber membrane prepared by the above method is composed of PVDF, surface-modified nano-TiO2 and PVP, and the surface is covered with a polydopamine coating; the average diameter of the nanofibers in the nanofiber membrane is 200-300 nm, the porosity of the membrane is 70-80%, and the water contact angle is less than 60°.

[0021] This invention further provides the application of the electrospun PVDF nanofiber membrane in wastewater treatment: the electrospun PVDF nanofiber membrane prepared above is used to treat wastewater containing organic pollutants and heavy metal ions. The specific wastewater treatment method is as follows: the nanofiber membrane is assembled into a membrane module, and wastewater is filtered using a cross-flow filtration method. The operating parameters of the cross-flow filtration are: wastewater flow rate 0.4-0.6 m / s, operating pressure 0.08-0.12 MPa.

[0022] For wastewater containing organic pollutants, such as methyl orange, under simulated sunlight irradiation, the nanofiber membrane can achieve a removal rate of over 95% for methyl orange at a concentration of 80-120 mg / L. For wastewater containing heavy metal ions, such as copper ions, the nanofiber membrane can achieve a retention rate of over 90% for copper ions at a concentration of 40-60 mg / L. When treating combined wastewater containing both organic pollutants and heavy metal ions, the nanofiber membrane achieves a removal rate of over 93% for organic pollutants and a retention rate of over 88% for heavy metal ions.

[0023] The beneficial effects of this invention are:

[0024] Enhanced hydrophilicity and antifouling properties: This invention introduces a polydopamine coating onto the surface of a PVDF nanofiber membrane. Polydopamine, with its abundant functional groups, can form hydrogen bonds with water molecules, significantly improving the hydrophilicity of the nanofiber membrane, reducing the water contact angle from 120° to below 60°. Simultaneously, the polydopamine coating effectively inhibits the adsorption of pollutants on the membrane surface, improving the membrane's antifouling properties and extending its service life.

[0025] Enhanced photocatalytic performance: The preparation method of this invention incorporates surface-modified nano-TiO2 particles. Surface modification enhances the interfacial bonding between nano-TiO2 and PVDF, improving the dispersion stability of nano-TiO2 in the PVDF matrix. Under simulated sunlight irradiation, nano-TiO2 can generate photogenerated electron-hole pairs, exhibiting photocatalytic degradation of organic pollutants. This, combined with the separation effect of the PVDF nanofiber membrane, significantly improves the removal efficiency of organic pollutants.

[0026] Highly efficient retention of heavy metal ions: The PVP in the nanofiber membrane prepared by this invention and the functional groups in the polydopamine coating can undergo complexation reactions with heavy metal ions, thereby achieving highly efficient retention of heavy metal ions. Simultaneously, the high specific surface area and suitable pore size distribution of the nanofiber membrane also contribute to improving the retention effect of heavy metal ions.

[0027] The preparation method is simple and low-cost: The preparation method of the present invention adopts common electrospinning technology and simple post-processing process, and the required equipment and raw material costs are low, making it easy to realize industrial production. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the preparation method of the nanofiber membrane of the present invention.

[0029] Figure 2 This is a photograph of the actual nanofiber membrane of the present invention.

[0030] Figure 3 This is an electron microscope image of the nanofiber membrane of the present invention.

[0031] Figure 4 This is a bar chart showing the effect of the nanofiber membrane of the present invention on the removal of methyl orange from wastewater.

[0032] Figure 5 This is a bar chart showing the effect of the nanofiber membrane of the present invention on the removal of copper ions in wastewater. Detailed Implementation

[0033] The following is in conjunction with the appendix Figure 1-5 The examples further illustrate the electrospun PVDF nanofiber membrane prepared according to the present invention and its effect in wastewater treatment.

[0034] Example 1

[0035] This embodiment provides an electrospun PVDF nanofiber membrane for wastewater treatment, and its preparation method is as follows:

[0036] Step 1: Preparation of spinning solution:

[0037] Accurately weigh 18g of PVDF particles and dissolve them in 82g of a mixed solvent consisting of N,N-dimethylformamide (DMF) and acetone in a volume ratio of 3:2. Place the mixture on a magnetic stirrer at 60°C and stir for 8 hours until the PVDF particles are completely dissolved to obtain a PVDF solution with a mass fraction of 18%.

[0038] Weigh 0.9 g of nano-TiO2 particles and disperse them in 50 mL of ethanol, then sonicate for 30 minutes. Next, add 0.09 g of 3-aminopropyltriethoxysilane (APTES) and stir at 50 °C for 4 hours. After the reaction, centrifuge the mixture at 10000 r / min for 10 minutes, discard the supernatant, wash the precipitate three times with ethanol, and then dry the precipitate in a vacuum drying oven at 60 °C for 12 hours to obtain surface-modified nano-TiO2 particles.

[0039] 0.9g of nano-TiO2 particles modified with 3-aminopropyltriethoxysilane (APTES) were added to the obtained PVDF solution and ultrasonically dispersed for 30 minutes. Then, 1.8g of polyvinylpyrrolidone (PVP) was added to the solution and stirred for 2 hours to obtain a uniform spinning solution.

[0040] Step 2, electrospinning:

[0041] The spinning solution was loaded into a syringe with a 22G metal needle. The syringe was installed on an electrospinning device. The electrospinning parameters were set as follows: voltage 20kV, distance between needle and collector 15cm, feed rate 0.5mL / h, ambient temperature 25℃, humidity 40%. The electrospinning device was started, and PVDF / TiO2 / PVP nanofiber membrane was obtained on the collector.

[0042] Step 3, Post-processing:

[0043] The PVDF / TiO2 / PVP nanofiber membrane was immersed in a 5% sodium hydroxide solution and treated at 30°C for 2 hours. Then it was rinsed with deionized water until neutral, and rinsed 3-5 times, with each rinse lasting 5-10 minutes.

[0044] The membrane was then immersed in a Tris-HCl buffer solution with a dopamine concentration of 2 mg / mL and a pH of 8.5. The reaction was carried out at room temperature for 12 hours to allow dopamine to self-polymerize on the membrane surface to form a polydopamine (PDA) coating. After the reaction was completed, the membrane was removed, rinsed with deionized water, and air-dried at room temperature to obtain the final electrospun PVDF nanofiber membrane.

[0045] Example 2

[0046] Treatment of wastewater containing methyl orange using electrospun PVDF nanofiber membranes:

[0047] Membrane module assembly: The electrospun PVDF nanofiber membrane prepared in Example 1 was cut into suitable sizes and assembled into a membrane module, which was then used for cross-flow filtration.

[0048] Wastewater treatment: A methyl orange (100 mg / L) solution was prepared and passed through a membrane module at a flow rate of 0.5 m / s and an operating pressure of 0.1 MPa, under simulated sunlight. Permeate samples were taken periodically, and the concentration of methyl orange in the permeate was measured using a UV-Vis spectrophotometer to calculate the removal rate. After 4 hours of treatment, the methyl orange removal rate reached 96.5%.

[0049] Example 3

[0050] Treatment of copper-containing wastewater using electrospun PVDF nanofiber membranes:

[0051] Membrane module assembly: The electrospun PVDF nanofiber membrane prepared in Example 1 was cut into suitable sizes and assembled into a membrane module, which was then used for cross-flow filtration.

[0052] Wastewater treatment: A copper sulfate solution with a concentration of 50 mg / L was prepared and passed through a membrane module at a flow rate of 0.5 m / s and an operating pressure of 0.1 MPa. Permeate samples were taken at regular intervals, and the concentration of copper ions in the permeate was determined using atomic absorption spectrometry to calculate the copper ion rejection rate. After 3 hours of treatment, the copper ion rejection rate reached 92.3%.

[0053] Comparative Example 1

[0054] Preparation and performance testing of PVDF nanofiber membranes without the addition of nano-TiO2 and without post-treatment:

[0055] 1. Preparation of spinning solution: Weigh 18g of PVDF particles and add them to 82g of a solvent made of DMF and acetone in a volume ratio of 3:2. Stir magnetically at 60℃ for 8 hours to obtain a PVDF solution with a mass fraction of 18%.

[0056] 2. Electrospinning: Following the same electrospinning steps as in Example 1, a PVDF nanofiber membrane without added nano-TiO2 was obtained.

[0057] III. Performance Testing: The membrane was used to treat wastewater containing methyl orange and copper ions, and the testing methods were the same as in Examples 2 and 3. The results showed that the removal rate of methyl orange was only 30.2%, and the retention rate of copper ions was 55.6%.

[0058] Comparative Example 2

[0059] Preparation and performance testing of PVDF nanofiber membranes without surface-modified nano-TiO2:

[0060] I. Preparation of spinning solution: Weigh 18g of PVDF particles and add them to 82g of a solvent composed of DMF and acetone in a volume ratio of 3:2. Stir magnetically at 60℃ for 8 hours to obtain a PVDF solution with a mass fraction of 18%. Then add 0.9g of unmodified nano-TiO2 particles, ultrasonically disperse for 30 minutes, and then add 1.8g of PVDF. Continue stirring for 2 hours to obtain the spinning solution.

[0061] II. Electrospinning and post-treatment: Following the same electrospinning and post-treatment steps as in Example 1, a PVDF nanofiber membrane without surface-modified nano-TiO2 was obtained.

[0062] III. Performance Testing: The membrane was used to treat wastewater containing methyl orange and copper ions, and the testing methods were the same as in Examples 2 and 3. The results showed that the removal rate of methyl orange was 75.3%, and the retention rate of copper ions was 70.1%.

[0063] Comparative Example 3

[0064] Preparation and performance testing of PVDF / TiO2 / PVP nanofiber membranes without dopamine coating post-treatment:

[0065] 1. Preparation of spinning solution and electrospinning: The preparation of spinning solution and electrospinning steps are the same as in Example 1 to obtain PVDF / TiO2 / PVP nanofiber membranes. The post-treatment in step 3 is not performed.

[0066] II. Performance Testing: The membrane was used to treat wastewater containing methyl orange and copper ions, and the testing methods were the same as in Examples 2 and 3. The results showed that the removal rate of methyl orange was 85.1%, the retention rate of copper ions was 80.5%, and the membrane had poor antifouling performance, with a significant decrease in flux during the treatment process.

[0067] The comparison of the examples and comparative examples shows that the electrospun PVDF nanofiber membrane prepared by the present invention has significant advantages in wastewater treatment, can efficiently remove organic pollutants and heavy metal ions, and has good anti-fouling performance.

Claims

1. A method for preparing an electrospun PVDF nanofiber membrane for wastewater treatment, characterized in that, The steps are as follows: Step 1: Preparation of spinning solution: Polyvinylidene fluoride (PVDF) particles were dissolved in a mixed solvent of N,N-dimethylformamide and acetone, and stirred at 55-65°C for 6-10 hours to obtain a PVDF solution with a mass fraction of 16-20%. Nano-TiO2 particles modified with 3-aminopropyltriethoxysilane were added to the obtained PVDF solution, wherein the mass of the nano-TiO2 particles was 3-7% of the mass of PVDF. Polyvinylpyrrolidone (PVP) was then added to the solution, wherein the mass of PVP was 8-12% of the mass of PVDF, and stirring was continued for 1-3 hours to obtain a uniform spinning solution. Step 2, electrospinning: The obtained spinning solution was loaded into a syringe with a metal needle and spun using an electrospinning device to obtain a PVDF / TiO2 / PVP nanofiber membrane on a collector. Step 3, Post-processing: The obtained PVDF / TiO2 / PVP nanofiber membrane was immersed in a 4-6% sodium hydroxide solution and treated at 28-32℃ for 1.5-2.5 hours, then rinsed with deionized water until neutral; the membrane was then immersed in a Tris-HCl buffer solution containing dopamine and reacted at room temperature for 10-14 hours, so that dopamine self-polymerized on the membrane surface to form a polydopamine coating, thus obtaining the final electrospun PVDF nanofiber membrane.

2. The method for preparing an electrospun PVDF nanofiber membrane for wastewater treatment according to claim 1, characterized in that: In step one, the volume ratio of N,N-dimethylformamide to acetone in the mixed solvent of N,N-dimethylformamide and acetone is 2.8-3.2:1.8-2.

2.

3. The method for preparing an electrospun PVDF nanofiber membrane for wastewater treatment according to claim 1, characterized in that: In step one, the surface modification method of the nano-TiO2 particles is as follows: the nano-TiO2 particles are dispersed in ethanol, 3-aminopropyltriethoxysilane is added, the mass ratio of 3-aminopropyltriethoxysilane to nano-TiO2 particles is 1:8-12, the reaction is stirred at 45-55℃ for 3-5 hours, and then centrifuged, washed and dried to obtain nano-TiO2 particles modified with 3-aminopropyltriethoxysilane.

4. The method for preparing an electrospun PVDF nanofiber membrane for wastewater treatment according to claim 3, characterized in that: The nano-TiO2 particles were dispersed in ethanol by ultrasonic dispersion for 25-35 minutes.

5. The method for preparing an electrospun PVDF nanofiber membrane for wastewater treatment according to claim 1, characterized in that: In step two, the metal needle is of model 20-24G; the electrospinning parameters are: voltage 18-22kV, distance between the needle and the collector 13-17cm, advance speed 0.4-0.6mL / h, ambient temperature 23-27℃, and humidity 35-45%.

6. The method for preparing an electrospun PVDF nanofiber membrane for wastewater treatment according to claim 1, characterized in that: In step three, the concentration of dopamine in the Tris-HCl buffer solution is 1.8-2.2 mg / mL, and the pH of the buffer solution is 8.3-8.

7.

7. The method for preparing an electrospun PVDF nanofiber membrane for wastewater treatment according to claim 1, characterized in that: In step three, the membrane treated with sodium hydroxide solution is rinsed with deionized water 3-5 times, with each rinse lasting 5-10 minutes.

8. An electrospun PVDF nanofiber membrane for wastewater treatment, characterized in that: The electrospun PVDF nanofiber membrane for wastewater treatment is prepared according to any one of claims 1-7. The electrospun PVDF nanofiber membrane is composed of PVDF, surface-modified nano-TiO2 and PVP, and the surface is covered with a polydopamine coating. The average diameter of the nanofibers in the nanofiber membrane is 200-300 nm, the porosity of the membrane is 70-80%, and the water contact angle is less than 60°.

9. The application of the electrospun PVDF nanofiber membrane for wastewater treatment according to claim 8, characterized in that: Used for wastewater treatment, the electrospun PVDF nanofiber membrane is used to treat wastewater containing organic pollutants and heavy metal ions.

10. A wastewater treatment method, characterized in that: The electrospun PVDF nanofiber membrane for wastewater treatment as described in claim 9 is assembled into a filter membrane module, and wastewater is filtered using a cross-flow filtration method. The operating parameters of the cross-flow filtration are: wastewater flow rate 0.4-0.6 m / s, and operating pressure 0.08-0.12 MPa.

Citation Information

Cited By

  • Nanofiber composite ultrafiltration membrane and gradient aperture preparation method thereof

    CN122006515A

  • Nanofiber composite ultrafiltration membrane and gradient pore diameter preparation method thereof

    CN122006515B